2012
DOI: 10.1029/2011gl049883
|View full text |Cite
|
Sign up to set email alerts
|

Bursty escape fluxes in plasma sheets of Mars and Venus

Abstract: [1] High resolution measurements of plasma in the plasma sheets of Mars and Venus performed by almost identical plasma instruments ASPERA-3 on the Mars Express spacecraft and ASPERA-4 on Venus Express reveal similar features of bursty fluxes of escaping planetary ions. A period of bursts lasts about 1-2 min. Simultaneous magnetic field measurements on Venus Express show that these burst-like features arise due to flapping motions of the plasma sheet. Their occurrence can be related to large-amplitude waves pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 28 publications
4
63
0
Order By: Relevance
“…Such bursts can be generated by different mechanisms but one suggestion is reconnection. Ions are seen moving alternately tailward and planetward, as the magnetic field changes in a way consistent with the spacecraft first entering and then leaving a magnetic island (Dubinin et al 2012). A clear example of the same geometry in presented by Zhang et al (2012).…”
Section: Magnetic Reconnection In the Magnetotailmentioning
confidence: 72%
See 1 more Smart Citation
“…Such bursts can be generated by different mechanisms but one suggestion is reconnection. Ions are seen moving alternately tailward and planetward, as the magnetic field changes in a way consistent with the spacecraft first entering and then leaving a magnetic island (Dubinin et al 2012). A clear example of the same geometry in presented by Zhang et al (2012).…”
Section: Magnetic Reconnection In the Magnetotailmentioning
confidence: 72%
“…Venus Express finally provided evidence that reconnection also occurs in the magnetotail of Venus (Zhang et al 2012;Dubinin et al 2012). Passing through the plasma sheet VEX observes spikes in electron and ion fluxes.…”
Section: Magnetic Reconnection In the Magnetotailmentioning
confidence: 98%
“…The observations of the CSs in the induced Martian magnetotail at different distances from the planet were reported in many studies based on data from different missions (e.g., Acuña et al, ; Dubinin et al, ; Dubinin & Fraenz, ; DiBraccio et al, ; Ferguson et al, ; Halekas et al, ; Harada et al, , ; Luhmann et al, ). It was shown that the dynamics of the Martian CS exhibits many features peculiar to the Earth's magnetotail CS: flapping motions (e.g., Dubinin et al, ; DiBraccio et al, , ), magnetic reconnection (Eastwood et al, ; Halekas et al, ; Harada et al, ) and associated plasma flow acceleration (Harada et al, ), and plasmoids formation (DiBraccio et al, ; Hara et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Bulk escape may be the primary source of plasma into the Martian plasma sheet, whereas ambipolar fields may be the primary driver for polar wind outflows of protons into the tail lobes (Dubinin et al 2011) and from other regions magnetically 'open' to interplanetary space. Magnetic reconnection may play a role in these loss mechanism (Eastwood et al 2008;Dubinin et al 2012). STATIC will provide the primary measurements of bulk ionospheric losses for the MAVEN mission, using composition to identify ionospheric components and resolving the transition from cold ionospheric ions to heated outflows.…”
Section: Introductionmentioning
confidence: 99%